Efficacy of Three-Dimensional Printing in the Management of Frontal Bone Trauma - Kassem, Mohamed; Hagras, Mahmoud Abd; Elsheikh, Mohamed Nasser; Erfan, Fathhe Ali; Amer, Mohamed (Journal of Neurological Surgery Part B: Skull Base, 2024)
Objectives Craniomaxillofacial (CMF) trauma surgery is difficult because of its unique architecture and vast range of injuries in the head and neck area. This study sought to determine the potential of employing preoperative three-dimensional (3D)-printed models to improve frontal fracture healing outcomes.Methods This prospective cohort clinical trial involved 20 patients who were surgically fitted and had a frontal bone fracture, as evidenced by computed tomography. The patients were separated into two groups: Group A: patients with frontal bone trauma reduced using 3D printing; and Group B: patients with frontal bone trauma reduced without 3D printing.Results Compared to Group B, Group A had a considerably shorter operational time (p < 0.001). The esthetic results, complications, and functional outcomes were not significantly different between the two groups. All patients in Groups A and B underwent accurate radiographic evaluations (correct placement of the titanium mesh).Conclusion 3D printing in preoperative planning improves frontal fracture repair with respect to operative length but does not reduce intraoperative blood loss or improve postoperative function compared with normal management.
Keywords: 3D printing; craniomaxillofacial; CT scan; Freihofer; frontal bone trauma